Low-Intensity Extracorporeal Shockwave Therapy – A New Approach in the Treatment of Erectile Dysfunction after Radical Prostatectomy - Boyan Stoykov; Nikolay Kolev; Rumen P.Kotsev; Fahd Al-Shargabi; Pencho Genov; Aleksandar Vanov (Journal of Biomedical & Clinical Research)
The experience accumulated with low-intensity extracorporeal shock wave therapy (LI-ESWT) from international clinical trials has demonstrated its safety, efficacy and good tolerance in treatment of erectile dysfunction (ED). The aim of this retrospective study was to investigate the effect of LI-ESWT in patients with ED after bilateral nerve sparing radical surgery for prostate cancer. Twenty-seven patients underwent bilateral nerve sparing radical retropubic prostatectomy (BNSRRP) at the clinic of urology of the university hospital in Pleven between January 2016 and December 2016. Twenty-one of these patients had pre-operative preserved erectile function (EF), as reported according to the International Index of Erectile Function (IIEF-5). Postoperatively, these 21 patients experienced a mild (18-21 points) impairment of EF. In 10 patients (group 1), LI-ESWT was performed. The procedure was performed once a week for 6 weeks with a LI-ESWT (BTL 6000 SWT Topline) instrument. The reading was obtained with IIEF-5 on the third and sixth month after the end of therapy. The other 11 patients (group 2) were used as a control group and did not receive treatment. In 5 patients in group 1, a recovery of EF (> 21 points) as per IIEF-5 was recorded at the third month after treatment. In two patients, the same score was recorded at the sixth month. No improvement was seen in three men in group 1. In the controls (group 2), a spontaneous EF improvement in four patients at sixth month was registered. Despite the small number of patients and their short-term follow-up, our initial results indicate that LI-ESWT is effective, safe and well-tolerated. It could be an alternative for early penis rehabilitation in patients who have undergone BNSRRP.